Building a Global Central Database for Promising Herbal Antimalarials from Various Countries: Strategies for Safe and Effective Drug Development (Global Journal of Medical Research, 2025)
Drug databases have become a critical tool used by various stakeholders to make informed decisions about medication therapy Globally researchers have carried out primary studies that have documented and provided knowledge on the antiplasmodial activities of numerous plants A central database designed to document vital efficacy and safety information on the most promising antimalarial-medicinal plants being recommended for advanced studies in the drug discovery and development pipeline is needed to serve as vital repository supporting the general public researchers academic institutions pharmacological companies policymakers and patients relying on herbal antimalarials Current malaria research programs require the use of advanced techniques in the development of new antimalarials
Keywords: global collaboration; central database; antimalarial-herbs and drugs; high-throughput and multi-omics screening; patients safety